546. Capturing Clinician's Experiences Repurposing Drugs to Inform Future Studies During COVID-19. (31st December 2020) - Duggal, Mili; Stone, Heather; Paul, Parvesh; Charles, Reema; Sacks, Leonard; Southall, Noel
Abstract: Background: CURE ID is an internet-based repository developed collaboratively by FDA and NCATS/NIH, with the support of WHO and IDSA. It encourages clinicians globally to share novel uses of existing drugs for patients with difficult-to-treat infections. It is designed to serve as a rapid communication platform for healthcare providers during an outbreak, providing for systematic case-sharing, discussion, and the latest literature. Besides case reports, CURE ID offers a discussion platform for clinicians, disease-specific clinical trials curated from clincialtrials.gov, and a newsfeed that shows relevant journal articles and news related to COVID-19 and other infectious diseases. Methods: The CURE ID team extracted individual case reports on patient-level treatments and outcomes of COVID-19 infection from the published literature and gathered clinician-submitted cases through the electronic case report form. Additionally, CURE ID partnered with the University of Pennsylvania's CORONA database to further populate the CURE ID database with published cases. Results: As of submission, lopinavir-Ritonavir (n=51) was the most commonly reported drug used. The following were also reported: hydroxychloroquine (n=31), azithromycin (n=28), arbidol (n=22), interferon alfa-2B (n=18), moxifloxacin (n=18), methylprednisolone (n=17), ivermectin (n=14), lopinavir (n=12), oseltamivir (n=12). The other drugs reported were danoprevir-ritonavir, intravenous immunoglobulins, interferon, interferon alfa, and tocilizumab. CURE ID currently includes more than 150 detailed COVID case reports of 65 repurposed drugs. We expect case reporting for specific drugs to be dynamic and additional data to accrue. Updated results will be presented. Conclusion: Several drugs are being repurposed to treat COVID-19. CURE ID gives clinicians an opportunity to share their treatment experiences and discuss their questions with a global community of healthcare providers. By utilizing the CURE ID platform, in conjunction with data gathered from other registries, observational studies and clinical trials, hypotheses can be generated that may inform future clinical trials and ultimately, potentially find safe and effective treatments for this deadly disease. Disclosures: All Authors : No reported disclosures